2018
DOI: 10.1182/bloodadvances.2018023713
|View full text |Cite
|
Sign up to set email alerts
|

A decreased and less sustained desmopressin response in hemophilia A carriers contributes to bleeding

Abstract: The cause of hemophilia A carrier bleeding is not well established. Desmopressin (DDAVP), used clinically to treat or prevent bleeding, can also be used as a medical stress surrogate. This study’s objective was to compare the response to DDAVP in hemophilia A carriers with that in normal control patients. Bleeding was assessed by the International Society on Thrombosis and Hemostasis Bleeding Assessment Tool (ISTH-BAT). DDAVP (0.3 μg/kg) was administered either IV or subcutaneously (SC), and blood was drawn at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…In accordance, a recent study in hemophilia carriers showed that participants with an abnormal bleeding score had a lower FVIII response to desmopressin compared with participants with a normal bleeding score. 16 Our current study and the previous analysis in hemophilia carriers show the important, underrated, role of hemostatic response to hemostatic challenges in patients with bleeding disorders. Individuals with comparable baseline hemostatic markers may have a different bleeding phenotype due to a difference in hemostatic response.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In accordance, a recent study in hemophilia carriers showed that participants with an abnormal bleeding score had a lower FVIII response to desmopressin compared with participants with a normal bleeding score. 16 Our current study and the previous analysis in hemophilia carriers show the important, underrated, role of hemostatic response to hemostatic challenges in patients with bleeding disorders. Individuals with comparable baseline hemostatic markers may have a different bleeding phenotype due to a difference in hemostatic response.…”
Section: Discussionsupporting
confidence: 57%
“…In hemophilia carriers, it was also found that FVIII levels 2 hours after desmopressin administration were associated with the bleeding phenotype, whereas there was no association with levels 1 and 4 hours after desmopressin administration. 16 Overall, these results may indicate that a sustained hemostatic response after hemostatic challenge is important to prevent bleeding or to decrease bleeding severity in patients with VWD.…”
Section: Vwf:agmentioning
confidence: 83%
See 2 more Smart Citations
“…These results compare favourably with the few data published on the response to DDAVP and its use in WGHA, 17,18 even if a recent study suggested a decreased and less sustained desmopressin response in WGHA. 19 This study has some limitations, namely the retrospective nature of data collection and the relatively small number of patients.…”
Section: Discussionmentioning
confidence: 97%